The Influence of The Teaching at The Right Level (Tarl) Approach on Basic Football Shooting Movement Skills - Aprilia, Farida Anesti; Pratama, Dani Slamet (JUMORA: Jurnal Moderasi Olahraga, 2024)
The purpose of this study was to determine the effect of using the TaRL method on the ability to shoot football in class XI TKR 1 students of SMK N 3 Semarang. The research method used is the classroom action research (CAR) technique. Participants in this study were class XI TKR 1 students of SMK N 3 Semarang. The results of this study indicate that the TaRL method has succeeded in improving the learning outcomes of shooting football in physical education learning. The initial percentage of students who successfully shot football before receiving TaRL intervention was 33.33%. After the TaRL intervention was implemented, the final percentage of students who successfully shot increased to 83.33%. The use of the TaRL method has been proven to improve the learning outcomes of shooting football movements. So there is an influence of the TaRL method on students' abilities